“Guarding Palupuh Forests”: Dutch Colonial Government`s Policies, Local Wisdom, and Forest Management in Nagari Koto Rantang, West Sumatra Province - Zubir, Zusneli; Sufyan, Fikrul Hanif; Ajisman, Ajisman; Refisrul, Refisrul; Novita, Rita (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2023)
The Batang Palupuh forest, part of the rimbo gadang (high forest) in Nagari Koto Rantang, Palupuh sub-district, has been part of a natuurmonument (nature reserve) since the Dutch colonial era to protect rare plant species. Long before it was designated as a nature reserve, the people of Koto Rantang with their local wisdom, had been protecting and caring for the forest for centuries. The method used was qualitative with an ethnoscience approach. The results show that the local knowledge of the community understands that the land in their area consists of rimbo gadang, paddy fields, parak, and fields. To utilise each land, especially for rice fields, parak, and ladang they have been guided by local knowledge, starting from determining the land, and the process of planting both long and short-term crops. And, since the management of the forest by the village authority in 2018, it has been developed with the tourism village programme of raflesia village, luak coffee, and rendang variants to domestic and foreign tourists.